Labor market costs for long-term family caregivers: the situation of caregivers of persons with spinal cord injury in Switzerland - Monica Ruoss; Mirjam Brach; Diana Pacheco Barzallo (BMC, 2023)
Abstract Background Family members are key in the provision of care to persons facing disability. To undertake the role as caregivers, they face many costs, being the setback in the labor market one of the most relevant. Methods We analyze comprehensive data from long-term family caregivers of persons with spinal cord injury (SCI) in Switzerland. Using information about their working situation before and after becoming caregivers, we estimated the reduction in working hours and the associated income loss. Results On average, family caregivers reduced their working hours by about 23% (8.4 h per week), which has a monetary value of CHF 970 per month (EUR 845). Women, older caregivers, and less educated caregivers have a much higher opportunity cost in the labor market: CHF 995 (EUR 867), CHF 1,070 (EUR 932), and CHF 1,137 (EUR 990) respectively. In contrast, family members who care for a person that works have a much lower impact on their working status, CHF 651 (EUR 567). Interestingly, the reduction in their working time is only a third of the extra work they face as caregivers. Conclusion Health and social systems rely on the unpaid work of family caregivers. To guarantee their long-term involvement, family caregivers need to be recognized for their work and potentially compensated. Without family caregivers, it is very unlikely societies can cope with the increasing need for care, as professional services are limited and expensive.